Affordability, security, sustainability? Grassroots community energy visions from Liverpool, United Kingdom. (December 2020) - Morrissey, J.; Schwaller, E.; Dickson, D.; Axon, S.
Highlights: Community visions of change pathways are key for support of transitions. Limited studies have explored community visions of energy transition. Envisioning provides an essential foundation for long-term policies and strategies. Distinct visions articulate ideals of energy system transition. Abstract: Envisioning societal futures for systemic low carbon transition is key to supporting the emergence of new configurations of the energy system. Such visions or 'imaginaries' facilitate wider societal support for system change. Given the urgency of the decarbonisation agenda, societal understandings of transitions processes and community ideas and visions about pathways for change assume a key role. The paper addresses an important gap in knowledge of place-based visions of energy system transition by soliciting views of community residents through a survey instrument, on what their perspectives on energy transition are. A case-study of Liverpool UK is presented, conducted as part of the EU Horizon 2020 ENTRUST project. Through a cluster analysis approach of study respondent perspectives, this study identities 4 distinct energy visions: (1) Community Affordability; (2) The Centre Ground; (3) Security First; and (4) Green Affordability. Identified visions present different perspectives on how energy is framed, with each vision characterised by distinct preferences on the extent to which stakeholder groups may influence the energy system as well as different views on the role of specific energy generation methods. Further, visions differ on the role of different actors and institutions in the energy transition. Identified energy visions provide insight into the ways in which grassroots communities consider how the energy system should transition in the coming years. The study contributes to understanding of spatially-situated and socially differentiated views of energy system transition, providing insight into contrasting viewpoints on current and future energy system priorities of residents of Liverpool, UK.